FEATURES OF CONSIDERATION AND RESOLUTION OF TAX DISPUTES IN THE LEGISLATION OF FOREIGN COUNTRIES - Yuldoshbekov Avazbek Alisher ugli (Scholar Express Journals, 2023)
The author of this article describes the theoretical and practical aspects of legal mechanisms for alternative dispute resolution. In this scientific work was carried out a systematic analysis of the norms of alternative resolution of tax disputes established by the Tax Code and other regulatory legal acts of the Republic of Uzbekistan, was conducted a comparative study of foreign experience in this area, were analyzed existing problems, were developed recommendations for their solution and were given proposals for improving legislation in the analyzed area. At the same time, has been analyzed the works, that carried out in our country on the alternative resolution of tax disputes, as well as on the prevention, identification and elimination of possible disputes in the tax area. Separately noted, that today the sphere of tax consulting in the country is being formed systematically and in stages. Also, author of this article analyzed the large-scale systematic work carried out to create a fair, transparent tax system for taxpayers and bring the system of alternative dispute resolution in line with international standards, as well as to strengthen the protection of the rights and legitimate interests of taxpayers
Keywords: tax authorities; taxpayer; consultation